(untitled) (CIPEEX, 2025)
A common chronic disease among children and adolescents, dental caries can trigger painful stimuli that tend to negatively influence school performance, social life and quality of life. The aim of this study is to describe the percentage of Brazilian school adolescents with dental pain over a 10-year period (2009-2019). This is a descriptive observational study using secondary data from the reports of the National School Health Survey - PeNSE carried out in 2009, 2012, 2015 and 2019 by IBGE and the Ministry of Health. The PeNSE sample consisted of 9th graders from public and private schools in the 26 Brazilian state capitals and the Federal District, aged between 13 and 17. Data was collected at the schools using a self-reported questionnaire. The variable of interest for this analysis was the experience of dental pain. The percentage of change in the report of dental pain between the years analyzed was calculated. The percentage of adolescents who reported dental pain in the six months prior to the survey was 15.9% in 2009, 18.5% in 2012, 20.0% in 2015 and 17.5% in 2019. There was an increase in the condition reported in the periods 2009 - 2012 (16.3%), 2012 - 2015 (8.1%) and in the total period of analysis between 2009 - 2019 (10.7%). The decrease in the prevalence of dental pain was observed in the years 2015 - 2019 (12%). There were changes in the research period related to the prevalence of dental pain among Brazilian school adolescents in the 10-year period from 2009 to 2019.